Biochemical characterization of the bifunctional enzyme dihydrofolate reductase-thymidylate synthase from Leishmania (Viannia) and its evaluation as a drug target (2013)
ABSTRACT : Introduction. Dihydrofolate reductase (DHFR) has been used successfully as a drug target in the area of anti-bacterial, anti-cancer and anti-malarial therapy. Although this bifunctional enzyme is also a potential drug target for treatment of leishmaniasis, there have been no reports on its efficacy against Leishmania (Viannia) species. Materials and methods. The gene encoding the bifunctional DHFR and thymidylate synthase (TS) of Le. (V.) braziliensis was isolated and expressed in E. coli. The enzyme was purified and characterized. The inhibitory effects of antifolates and four aporphine alkaloids on its activity were evaluated. Results. The full-length gene consists of a 1560-bp open reading frame encoding a 58 kDa translated peptide containing DHFR and TS domains linked together in a single polypeptide chain. The recombinant DHFR-TS enzyme revealed Km and Vmax values of 55.35 ± 4.02 μM (mean ± SE) and 0.02 ± 5.34 x 10-4 μM/min respectively for dihydrofolic acid (H2 F). The Le. braziliensis rDHFR-TS have Ki values for antimicrobial antifolates in the µM range. Methotrexate (MTX) was a more-potent inhibitor of enzymatic activity (Ki = 22.0 µM) than trimethoprim (Ki = 33 µM) and pyrimethamine (Ki = 68 µM). These Ki values are significantly lower than those obtained for the aporphine alkaloids. Conclusion. The results of the study show the inhibitory effect of antifolate drugs on enzymatic activity, indicating that Le. braziliensis rDHFR-TS could be a model to studying antifolate compounds as potential antiprotozoal drugs.